SAT0647 Predictive factors of positive positron emission tomography for diagnosing aortitis in patients with polymyalgic syndrome. (12th June 2018) - Prieto-Peña, D.; Loricera, J.; Martínez-Rodríguez, I.; Banzo, J.; Calderón-Goercke, M.; Calvo-Río, V.; González-Vela, C.; González-Gay, M.; Blanco, R.; Hernández, J.
Abstract : Background: Isolated non-infectious aortitis is a potentially serious condition whose diagnosis is often delayed due to the non-specific nature of its symptoms. Most of the patients initially present with polymyalgic syndrome associated with atypical symptoms. Nowadays 18 F-FDG PET/CT scan is the best tool for early detection of aortitis. However, it is a complex and expensive technique. Thus, we should make an effort to select those patients who will benefit the most from this procedure. Unfortunately, we have no data about which factors may improve the probability of a positive diagnosis of aortitis using this imaging technique. Objectives: Our aim was to evaluate, in patients with polymyalgia rheumatica (PMR), the predictive factors for a positive 18 F-FDG PET/CT scan, in order to make an early diagnosis of aortitis and optimise the use of this technique. Methods: Retrospective study on 97 patients with PMR who had undergone an 18 F-FDG PET/CT scan between January 2010 and August 2017 with a high clinical suspicion of aortitis. Only patients with polymyalgic syndrome without any other underlying disease were included. We considered two groups: a) Classic PMR: patients who fulfilled the 2012 EULAR/ACR criteria; and b) Atypical PMR: patients with symptoms resembling PMR but did not fulfil the 2012 EULAR/ACR criteria. Distribution of categorical variables was compared by the Pearson Chi-squared test or Fisher exact test. Quantitative variables were analysed using the Student t test or Mann Whitney U test as appropriate. An adjusted logistic regression model was built to assess the best set of predictive factors for a positive PET scan in both groups of patients. Results: 18 F-FDG PET/CT scans were performed in 97 patients due to clinical suspicion of aortitis, being positive in 60 (61.9%). Patients (60 women/37 men) had a mean age of 68.4±10.7 years. Fifty-one (52.6%) had classic PMR and 46 (47.4%) atypical PMR. In patients with classic PMR, the best set of predictors for a positive PET/CT scan were lower limb pain (OR=8.4, 95% CI 2.0–35.1; p=0.004) and low back pain (OR=7.6, 95% CI 1.3–45.5, p=0.027), once adjusted for age, sex and current tobacco use. In atypical PMR patients, only the pelvic girdle affection (OR: 5.0, 95% CI 1.3–19.5; p=0.002) was significantly associated with a positive PET/CT scan, in the logistic adjusted model. Conclusions: We have found that, in patients with classic PMR, the presence of diffuse lower limb pain and inflammatory low back may have clinical relevance when requesting a PET/CT scan due to aortitis suspicion. On the other hand, in patients with atypical PMR, only the presence of pain in the pelvic girdle seems to be a predictive factor for a positive result in PET/CT scan. Disclosure of Interest: None declared